2016
DOI: 10.18632/oncotarget.10923
|View full text |Cite
|
Sign up to set email alerts
|

IRES-dependent translation of the long non coding RNA meloe in melanoma cells produces the most immunogenic MELOE antigens

Abstract: MELOE-1 and MELOE-2, two highly specific melanoma antigens involved in T cell immunosurveillance are produced by IRES-dependent translation of the long « non coding » and polycistronic RNA, meloe. In the present study, we document the expression of an additional ORF, MELOE-3, located in the 5′ region of meloe. Data from in vitro translation experiments and transfection of melanoma cells with bicistronic vectors documented that MELOE-3 is exclusively translated by the classical cap-dependent pathway. Using a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 26 publications
1
29
0
1
Order By: Relevance
“…Researchers demonstrated that the lncRNA MELOE produced three polypeptides, MELOE-1, MELOE-2, and MELOE-3, of 39, 44, and 54 aa long, respectively [55][56][57]. MELOE RNA was shown to be polycistronic, and translation of MELOE-1 and MELOE-2 depends on internal ribosome entry site (IRES) sequences [58], while MELOE-3 is translated via a classical cap-dependent mechanism.…”
Section: Meloementioning
confidence: 99%
“…Researchers demonstrated that the lncRNA MELOE produced three polypeptides, MELOE-1, MELOE-2, and MELOE-3, of 39, 44, and 54 aa long, respectively [55][56][57]. MELOE RNA was shown to be polycistronic, and translation of MELOE-1 and MELOE-2 depends on internal ribosome entry site (IRES) sequences [58], while MELOE-3 is translated via a classical cap-dependent mechanism.…”
Section: Meloementioning
confidence: 99%
“… 33 Indeed, by transferring miR-503 from the endothelium to the tumor microenvironment, thus interfering with interaction between breast cancer (BC) cells and the microenvironment, endothelial exosomes contribute to chemotherapeutic response in BC. 25 In addition, exosome-transferred miR-21 derived from M2-polarized macrophages confer cisplatin resistance in GC, suggesting a new therapeutic strategy for GC patients 34 , 35 , 36 ( Table 1 ).…”
Section: Main Textmentioning
confidence: 99%
“…As a result, ITAFs play an important role in determining the cell- or tissue-specific expression of polycistronic transcripts with IRESs. For example, in meloe, two IRESs code for T-cell antigens that are selectively expressed in melanoma cells but are absent in melanocytes, suggesting that ITAFs are silenced in normal melanocytes [15, 16]. In tissues that do not express or sequester ITAFs critical for IRES function, it would be expected that the polycistronic gene would function in a monocistronic manner, highly reliant on cap-dependent translation.…”
Section: Regulation Of Cellular Ires Activitymentioning
confidence: 99%
“…Differential expression of ITAFs between normal melanocytes and melanoma cells could also account for the activation of these antigens selectively in cancer cells [15]. Furthermore, an additional ORF was identified in the 5’ region of meloe coding for MELOE-3, translated by a cap-dependent pathway [16]. MELOE-3 was found to have poor immunogenicity, suggesting the importance of targeting the IRES-dependent proteins MELOE-1 and MELOE-2 for immunotherapy of melanoma.…”
Section: Why Polycistronic Genes?mentioning
confidence: 99%